Minimally invasive technique for the correction of luxation of the lens into the vitreous and in-the-bag IOL implantation - Zhmuryk, D.V. (Ukrainian Journal of Ophthalmology, 2026)
Background: The availability of a variety of the methods proposed for the removal of luxated lens and implantation of the intraocular lens (IOL) can make us conclude that, currently, there is no unified surgical tactics for this disorder. Purpose: To develop a minimally invasive technique for the correction of luxation of the lens into the vitreous and in-the-bag IOL implantation. Materials and Methods: Twenty five patients were operated on for the lens luxation secondary to ocular contusion and followed up for a mean of 3 years during September 2011 to February 2016 at the Kyiv Eye Microsurgery Center. Preoperatively, the mean best-corrected visual acuity (BCVA) was 0.14 ±0.16 (range, light perception with accurate projection to 0.5), and the mean intraocular pressure (IOP) was 19.74 ± 2.64 mmHg (range, 18 to 27 mmHg). Results: At day 2, month 1, month 3, month 6, and month 12 following surgery, the BCVA was 0.37 ± 0.21, 0.54 ± 0.20, 0.58 ± 0.23, 0.56 ± 0.22 and 0.57 ± 0.19, respectively (Table 1), and surgically induced astigmatism averaged 1.31 ± 0.62 D, 0.95 ± 0.36 D, 0.75 ± 0.31 D, 0.61 ± 0.25 D and 0.56 ± 0.22 D, respectively. Conclusions: The technique presented allows the surgeon to remove the lens through a small self-sealing incision, with a low incidence of intraoperative and postoperative complications; to implant any soft IOL designs; to restore the normal structure of the eye; and to make an IOL stable and well-centered, with surgically induced astigmatism averaged 0.56±0.22 D and preservation of or improvement in visual acuity to 0.5 or better at the 12 months.